ANALISIS PERSEPSI PELANGGAN TERHADAP DAMPAK PARKIR LIAR DI KAWASAN KOPI STUDIO 24 KOTA MALANG - Launasya Lintang Andrawina; Raja Dayana; Saskia Arta Mega; Afra Salsabila Hasna; Luhur Wahyu Aji (Ndrumi : Jurnal Ilmu Pendidikan dan Humaniora, 2026)
The prevalence of illegal parking practices around Kopi Studio 24, Klojen, Malang City has caused considerable concern among customers, necessitating an in-depth study of the issue. This study aims to: (1) identify the perspectives of Kopi Studio 24 customers toward illegal parking practices without official tickets in the area, and (2) describe customer behavior in responding to illegal parking fee collection. This study employed a descriptive qualitative approach with data collected through open-ended questionnaires distributed to 28 respondents from November 14-16, 2025. The findings reveal that: (1) customers perceive illegal parking as a violation of regulations that is detrimental to consumers and causes discomfort during their visits; (2) customers tend to pay the parking fees not out of willingness, but due to the absence of legitimate parking alternatives and fear of negative reactions from parking attendants upon refusal. Customers expressed hope that the café management would promptly establish a formal, transparent, and affordable parking system.